Conocimientos, gustos y prácticas sobre el consumo de lácteos en una población escolar de la ciudad de Medellín-Colombia (2014)
ABSTRACT: Dairy products intake is important for children’s health and development. However, in developing countries, it does not reach WHO recommendation; 180 L/person/y. Objective: To determine the knowledge, preference and practices associated with dairy products intake in school population from Medellin, comparing with soft drinks intake. Methods: personal interviews were obtained from 384 children, 7 and 12 y old, from 9 elementary schools. Differences between dairy and soft drink were evaluated by MANOVA, using SAS version 9.0. Results: Mean dairy products intake was 135.5 L/person/y. Differences between gender (p=0.53), or socio-economical level (p=0.17) were not detected. Only 38.2% of children know daily products intake recommendation and 42% knows its nutritional content. Taste was the main motivation for intake in 60.4% of children. Mean soft drink intake was and 137.7 L/person/y. Conclusions: It is necessary to enhance students’ knowledge about the importance of dairy products’ for health,and to implement educational campaigns to promote their consumption.